Skin-infiltrating T cells display distinct inflammatory signatures in lichen planus, bullous pemphigoid and pemphigus vulgaris - Schinner, Jona; Cunha, Tomas; Mayer, Johannes U.; Hörster, Stefan; Kind, Peter; Didona, Dario; Keber, Corinna; Hertl, Michael; Worzfeld, Thomas; Juratli, Hazem A. (Frontiers in Immunology, 2023)
Introduction: We here thought to dissect the inflammatory signature in lesions of three skin disorders, which show a common adaptive immune response against autoantigens of the skin but are characterized by diverging clinical phenotypes. Pemphigus vulgaris (PV) and bullous pemphigoid (BP) are type-2-dependent, IgG autoantibody-driven blistering disorders of mucous membranes and skin, which target desmoglein (Dsg)3 and bullous pemphigoid (BP)180, respectively. In contrast, lichen planus (LP) is a common chronic inflammatory disease of the skin and mucous membranes with a pronounced dermal T cell infiltrate. We previously identified peripheral type 1 and 17 T cell responses against Dsg3 and BP180 in a cohort of LP patients strongly suggesting that the underlying inflammatory T cell signature may drive the evolving phenotype. Methods: Paraffin-embedded skin biopsies from well-characterized patients with LP (n=31), BP (n=19), PV (n=9), and pemphigus foliaceus (PF) (n=2) were analysed. Areas with the most prominent inflammatory infiltrate were excised with punch biopsies and tissue microarrays (TMA) containing multiple biopsies were created. Using multicolor immunofluorescence, the inflammatory infiltrate was stained with antibodies against multiple cellular markers, i. e. CD3ε, CD4, CD15, TCR-δ, the cytokine IL-17A, and the transcription factors, T-bet and GATA-3. Results: In LP, there was a higher number of CD4+ T cells expressing T-bet compared to GATA-3. In contrast, CD4+ T cells in PV and BP skin lesions more frequently expressed GATA-3 than T-bet. IL-17A+ cells and IL-17A+ T cells were found to a similar extent in all the three disorders. IL-17A+ granulocytes were more predominant in BP than in LP or PV. Of note, the majority of IL-17A+ cells in LP were neither T cells nor granulocytes. Discussion: Our findings in inflammatory skin infiltrates clearly show a predominant type 1 signature in LP in contrast to a preponderance of type 2 T cells in PV and BP. In contrast to LP, granulocytes and to a much lesser extent CD3+ T cells were a cellular source of IL-17A in BP and PV. These data strongly suggest that different inflammatory cell signatures drive evolving clinically diverse phenotypes of LP, PV and BP despite common target antigens of the skin.